Effect of NaCl on Biofilm Formation of the Isolate from Staphylococcus aureus Outbreak Linked to Ham - Lee, Soomin; Choi, Kyoung-Hee; Yoon, Yohan (Korean journal for food science of animal resources, 2014)
The objective of this study was to evaluate the effects of NaCl on the biofilm formations of the isolate from Staphylococcus aureus outbreaks linked to ham. The S. aureus ATCC13565 isolated from ham was exposed to NaCl concentrations of 0%, 2%, 4%, and 6% supplemented in tryptic soy broth (TSB) for 24 h at 35℃, followed by plating 0.1 mL of the culture on tryptic soy agar containing 0%, 2%, 4%, and 6% NaCl, respectively. After incubating at 35℃ for 24 h, the colonies on the plates were collected and diluted to OD600 = 0.1. The diluents of S. aureus were incubated on a 96-well flat bottom plate containing TSB plus the appropriate NaCl concentrations, and the biofilm formation was quantified by crystal violet staining after being incubated at 35℃ for 9 h. Confocal laser scanning microscope (CLSM) was also used for visualizing the biofilm formation of S. aureus at NaCl concentrations of 0%, 2%, 4%, and 6%. The transcriptional analysis of biofilm-related genes, such as icaA, atl, clfA, fnbA, sarA, and rbf, was conducted by quantitative real-time PCR. Crystal violet staining and CLSM showed that the biofilm formations of S. aureus increased (p<0.05) along with the NaCl concentrations. Moreover, the expression of the icaA genes was higher at the NaCl concentrations of 4% and 6% as compared with 0% of NaCl by approximately 9-folds and 20-folds, respectively. These results indicated that the NaCl formulated in processed food may increase the biofilm formations of S. aureus by increasing the icaA gene expressions.